Data Reconciliation in DHT Networks - Martins, Vidal; Pacitti, Esther (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2007)
Optimistic replication can provide high data availability for collaborative applications in large scale distributed systems (grid, P2P, and mobile systems). However, if data reconciliation is performed by a single node, data availability remains an important issue since the reconciler node can fail. Thus, reconciliation should also be distributed and reconciliation data should be replicated. We have previously proposed the DSR-cluster algorithm, a distributed version of the IceCube semantic reconciliation engine designed for cluster networks. However DSR-cluster is not suitable for P2P networks, which are usually built on top of the Internet. In this case, network costs must be considered. The main contribution of this paper is the DSR-P2P algorithm, a distributed reconciliation algorithm designed for P2P networks. We first propose a P2P-DHT cost model for computing communication costs in a DHT overlay network. Second, taking into account this model, we propose a cost model for computing the cost of each reconciliation step. Third, we propose an algorithm that dynamically selects the best nodes for each reconciliation step. Our algorithm yields high data availability with acceptable performance and limited overhead.